Oral squamous cell carcinoma (OSCC) tumors from heavy alcohol consumers are associated with higher levels of TLR9 and a particular immunophenotype: Impact on patient survival - Bolesina, Nicolás (2022)
Fil: Bolesina, Nicolás. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Estomatología. Departamento de Patología Oral; Argentina.